Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

In-situ transformation of layered double hydroxide precursors into CeF3@Ni3Fe catalysts via anion-mediation for hydrogen storage in MgH2 - Mei Tang; Jiakun Yang; Ruolin Zhao; Xiuyu Yue; Haizhen Liu; Jin Guo; Zhiqiang Lan (Chemical Engineering Journal, 2026)

Life-time levonorgestrel exposure causes intergenerational alterations of the thyroid-catecholaminergic–GABAergic functional network in zebrafish (Danio rerio) - Xing Hu; Qianlin Cai; Junhao Wu; Meixin Ye; Jinlin Yang; Hao Huang; Weiyi Liang; Yutong Zhang; Ruolin Shi; Yazi Liu; Liping Hou; Diyun Chen (Environmental Research, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Unlocking catalytic capacity of (S)-selective ω-transaminases toward aryl methyl ketones via pocket engineering and droplet screening - Ping Gui; Xiao Li; Wangtao Jiang; Ruolin Yang; Peiyao Chang; Xingwang Qie; Xinrui Wang; Xuefeng Wang; Jingjie Jiang; Liyan Wang; Xiaojie Guo; Hongbin Zou; et al. (Bioresource Technology, 2026)

High-entropy heterogeneous design enables ultra-fatigue-resistant gel elastomers for multimodal sensing and intelligent human-machine interaction - Ruolin Wang; Baijie Cheng; Yexi Jin; Ying Xu; Jiajia Yang; Xihua Lu (Chemical Engineering Journal, 2026)

CeO2 nanoparticles-embedded hierarchical porous C/SiO2 for efficient catalytic amine regeneration in CO2 capture - Ling Liu; Yunrong Zhang; Yingying Zhang; Qi Dong; Yanyang Xue; Wanyi Ding; Fei Yang; Guo-Jun Kang; Ruolin Cheng; Shi-Jian Lu (Journal of Environmental Chemical Engineering, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Luminescence dating of core sediments from the southern coastal Bohai Sea, China, and its implications for transgression history during the Late Quaternary - Zhiqiang Xu; Yang Han; Bingpeng Yan; Mingbo Li; Ruolin Jiang; Ruonan Tian; Bohui Liu; Zihui Zhu; Weitao Yuan; Zhongping Lai (Frontiers in Marine Science, 2025)
Several marine strata have developed along the southern coastal Bohai Sea since the Late Quaternary, preserving abundant records of sedimentary evolution. This region is ideal for studying the sedimentary history of a river–sea interaction area. However, detailed sedimentological and chronological studies remain limited, mainly focusing on the estuaries of the Mihe River. In this study, 12 optically stimulated luminescence (OSL) samples were collected from the upper 20 m of a 101 m core to establish a chronological framework using quartz OSL dating. Grain-size analysis was also conducted to determine sedimentological characteristics. Results indicate that the quartz OSL ages range from >100 ka to 6.2 ± 0.4 ka, and we believe they were the minimum ages when equivalent dose (D e ) >ca. 250 Gy (sample DZK3-G07 and below) owing to OSL signal saturation. Our findings reveal a sedimentary hiatus between >100 ka and 19.8 ka. Holocene sediments are found above a depth of 8.4 m with an onset age of approximately 10.5 ka. A lacustrine layer (8.4–9.6 m) in core DZK3 was dated to 19.8–10.5 ka, which is much older than that of the limnetic and lagoon layers in other cores in this area. Based on sedimentary facies and dating results, no transgressive sediments were observed during marine isotope stage (MIS) 3, and T2 (Xianxian transgression) in the southern coastal Bohai Sea only occurred in MIS 5e. This sedimentary sequence pattern is consistent with global sea-level changes.

The environmental concentration of diethylstilbestrol and its structural analogues promote the conjugation transfer of ARGs through the pheromone effect - Panpan Yang; Xiaobo Yang; Feng Wang; Rumeng Li; Man Zhang; Jingxue Qian; Ruolin Hao; Zhiqiang Shen; Jingfeng Wang; Lijuan Zhang; Zhigang Qiu; Yanhua Cao (Journal of Hazardous Materials, 2025)

Effects of okadaic acid on Pyropia yezoensis: Evidence from growth, photosynthesis, oxidative stress and transcriptome analysis - Ruolin Wu; Jiangbing Qiu; Xianghai Tang; Aifeng Li; Yongmeng Yang; Xinyu Zhu; Xianyao Zheng; Wenke Yang; Guangyao Wu; Guixiang Wang (Journal of Hazardous Materials, 2025)

Precipitation recycling impacts on runoff in arid regions of China and Mongolia: a machine learning approach - Ruolin Li; Qi Feng; Yang Cui (Hydrological Sciences Journal, 2025)

Lower toxicity of HFPO-DA compared to its predecessor PFOA to the earthworm Eisenia fetida: Evidence from oxidative stress and transcriptomic analysis - Ruolin Wu; Xiaole Wang; Jingwen Zhang; Chengbo Lu; Bing Li; Zhongkun Du; Jun Wang; Jinhua Wang; Yue Yang; Lusheng Zhu (Journal of Hazardous Materials, 2025)

Effect of enzymatic hydrolysis on flavor enhancement of yogurt fermented by lactic acid bacteria in egg white - Qing Gao; Ruolin Xu; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Bioscience, 2025)

Equivalent spring model and efficient numerical strategy for simulating mechanical performance of seam-clip connections in aluminum alloy high-vertical standing seam metal cladding systems - Qisheng Liang; Qingshan Yang; Min Liu; Ruolin Liu; Wei Chen (Engineering Structures, 2025)

Characterization of liquid egg yolks hydrolyzed by phospholipase: Structure, thermal stability and emulsification properties - Ruolin Xu; Qing Gao; Junhua Li; Yujie Su; Luping Gu; Yanjun Yang; Cuihua Chang (Food Research International, 2024)

Functional analysis of a rice 12-oxo-phytodienoic acid reductase gene (OsOPR1) involved in Cd stress tolerance - Longying Wu; Ruolin Wang; Mingyu Li; Zhiye Du; Yufan Jin; Yang Shi; Wenjun Jiang; Ji Chen; Yuan Jiao; Binhua Hu; Jin Huang (Molecular Biology Reports, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Towards in-site carbon utilization and highly efficient nutrients removal: Effects of ammonium on the phosphorus recovery performance in a biofilm-based system - Zhen Bi; Ruolin Ding; Yong Huang; Yang Pan (Journal of Water Process Engineering, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Oxidation of emerging contaminants by S(IV) activated ferrate: Identification of reactive species - Yingying Chu; Mujian Xu; Xiaoyang Li; Junhe Lu; Zhichao Yang; Ruolin Lv; Jiahang Liu; Lu Lv; Weiming Zhang (Water Research, 2024)

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Responses of the intestinal microbiota to exposure of okadaic acid in marine medaka Oryzias melastigma - Yongmeng Yang; Aifeng Li; Jiangbing Qiu; Dongmei Gao; Chao Yin; Dongyue Li; Wenhui Yan; Hui Dang; Peiyao Li; Ruolin Wu; Lilin Han; Xiaoyun Wang (Journal of Hazardous Materials, 2024)

Effects of particle size on the pyrolysis of waste tires during molten salt thermal treatment - Ruolin Li; Yang Ren; Chengyang Cao; Chao He; Hongyun Hu; Xian Li; Hong Yao (Fuel, 2024)

An Underwater Image Restoration Deep Learning Network Combining Attention Mechanism and Brightness Adjustment - Jianhua Zheng; Ruolin Zhao; Gaolin Yang; Shuangyin Liu; Zihao Zhang; Yusha Fu; Junde Lu (Journal of Marine Science and Engineering, 2023)
This study proposes Combining Attention and Brightness Adjustment Network (CABA-Net), a deep learning network for underwater image restoration, to address the issues of underwater image color-cast, low brightness, and low contrast. The proposed approach achieves a multi-branch ambient light estimation by extracting the features of different levels of underwater images to achieve accurate estimates of the ambient light. Additionally, an encoder-decoder transmission map estimation module is designed to combine spatial attention structures that can extract the different layers of underwater images’ spatial features to achieve accurate transmission map estimates. Then, the transmission map and precisely predicted ambient light were included in the underwater image formation model to achieve a preliminary restoration of underwater images. HSV brightness adjustment was conducted by combining the channel and spatial attention to the initial underwater image to complete the final underwater image restoration. Experimental results on the Underwater Image Enhancement Benchmark (UIEB) and Real-world Underwater Image Enhancement (RUIE) datasets show excellent performance of the proposed method in subjective comparisons and objective assessments. Furthermore, several ablation studies are conducted to understand the effect of each network component and prove the effectiveness of the suggested approach.

Electronic nose application for detecting different odorants in source water: Possibility and scenario - Yongjing Wang; Xinyu Yan; Songtao Wang; Song Gao; Kai Yang; Ruolin Zhang; Mengshu Zhang; Moru Wang; Lianhai Ren; Jianwei Yu (Environmental Research, 2023)

An R2R3-MYB FtMYB11 from Tartary buckwheat has contrasting effects on abiotic tolerance in Arabidopsis - Qian Chen; Lu Peng; Anhu Wang; Lingzhi Yu; Yu Liu; Xinrong Zhang; Ruolin Wang; Xiaoyi Li; Yi Yang; Xufeng Li; Jianmei Wang (Journal of Plant Physiology, 2023)

Toxicity comparison of atrazine on Eisenia fetida in artificial soil and three natural soils - Xiaoying Li; Yue Yang; Ruolin Wu; Kaixuan Hou; Samuel C. Allen; Lusheng Zhu; Zhongkun Du; Bing Li; Jinhua Wang; Jun Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Isotopic fingerprinting of dissolved iron sources in the deep western Pacific since the late Miocene - Ruolin Liu; Bai Guo; Maoyu Wang; Weiqiang Li; Tao Yang; Hongfei Ling; Tianyu Chen (Science China Earth Sciences, 2020)